The Transformation of Education from Home to Kuttab: Early Islamic Educational Institutions in the Time of the Prophet PBUH - Al Ghifari, Mahdini; Anugerah, Muhammad Ruvi; Muhajir, Sapuani; Roza, Ellya (Journal of English Language and Education, 2026)
Islamic education during Prophet Muhammad's (PBUH) era evolved from secretive home-based learning in Mecca to structured institutions in Medina amid social-political challenges. This study aims to analyze this transformation from home and Dar al-Arqam to mosque, Suffah, and Kuttab for adaptive modern models. It employs qualitative systematic literature review (SLR) via PRISMA, targeting literature on early Islamic education (1972-2025) from Google Scholar and Scopus; purposive sampling yielded 30 sources until theoretical saturation. Instruments include documentation and content observation, analyzed via Miles-Huberman's reduction-display-conclusion with source triangulation. Findings reveal dynamic shifts: Dar al-Arqam for tauhid foundations, mosques for multifunctional halaqah, Suffah for poor scholars' regeneration, and post-Badr Kuttab for Quranic literacy. In conclusion, this holistic, adaptive model integrates faith, knowledge, and skills, offering curriculum reconstruction for digital disruptions.